Pemanfaatan Skrining dan Penyuluhan Kesehatan untuk Optimalisasi Penanganan Anemia pada Usia Remaja - Defi Nurul Hayati; Kurnia Ritma Dhanti; Eqwar Saputra; Tuflayfah Khasanah; Anisa Putri Salsabila (Forum Kerjasama Pendidikan Tinggi, 2025)
Anemia is when the body does not have enough healthy red blood cells. This condition occurs due to reduced hemoglobin (an iron-rich protein) which affects the production of red cells. Anemia is a health problem throughout the world and currently, the prevalence of anemia in adolescents is still high. The impact of anemia on teenagers is a decrease in: productivity, fitness, concentration, and decreased immunity as well as disrupting growth. Lack of information delivery, parental, community, and government concern for adolescent health as well as inadequate adolescent health services are also the reasons why this problem cannot be resolved. This community service aims to increase the knowledge of students at SMA Muhammadiyah 1 Purbalingga regarding anemia and to screen for anemia by checking hemoglobin levels for early detection of anemia. The method used is interactive lectures and questions and answers, to check hemoglobin levels using the Point of Care Testing (POCT) method. The results of data analysis showed that there was a significant difference between before and after providing anemia screening education to students at SMA Muhammadiyah 1 Purbalingga (p<0.05) with an average of 45 before the education was provided to 80 after the education. The conclusion is that health education regarding anemia screening has increased the knowledge of young women at SMA Muhammadiyah 1 Purbalingga.